Development of the IBD Disk: A Visual Self-administered Tool for Assessing Disability in Inflammatory Bowel Diseases. Issue 3 (31st January 2017) - Ghosh, Subrata; Louis, Edouard; Beaugerie, Laurent; Bossuyt, Peter; Bouguen, Guillaume; Bourreille, Arnaud; Ferrante, Marc; Franchimont, Denis; Frost, Karen; Hebuterne, Xavier; Marshall, John K.; O'Shea, Ciara; et al.
Abstract : Background: The Inflammatory bowel disease (IBD) Disability Index is a validated tool that evaluates functional status; however, it is used mainly in the clinical trial setting. We describe the use of an iterative Delphi consensus process to develop the IBD Disk—a shortened, self-administered adaption of the validated IBD Disability Index—to give immediate visual representation of patient-reported IBD-related disability. Methods: In the preparatory phase, the IBD CONNECT group (30 health care professionals) ranked IBD Disability Index items in the perceived order of importance. The Steering Committee then selected 10 items from the IBD Disability Index to take forward for inclusion in the IBD Disk. In the consensus phase, the items were refined and agreed by the IBD Disk Working Group (14 gastroenterologists) using an online iterative Delphi consensus process. Members could also suggest new element(s) or recommend changes to included elements. The final items for the IBD Disk were agreed in February 2016. Results: After 4 rounds of voting, the following 10 items were agreed for inclusion in the IBD Disk: abdominal pain, body image, education and work, emotions, energy, interpersonal interactions, joint pain, regulating defecation, sexual functions, and sleep. All elements, except sexual functions, were included in the validated IBD Disability Index. Conclusions: The IBD Disk has the potential to be a valuable tool for use at a clinical visit. It can facilitate assessment of inflammatory bowel disease-related disability relevant to both patients and physicians, discussion on specific disability-related issues, and tracking changes in disease burden over time.